A new species of Achelia (Pycnogonida: Ammotheidae) and first records of intertidal sea spiders found on Zoanthus (Cnidaria: Zoantharia) from Karachi, Pakistan - George, Zarish; Siddiqui, Ghazala; George, Nazish; Lucena, Rudá Amorim (Zootaxa, 2020)
Ten intertidal sea spider (Pycnogonida) species from five families - Pycnogonidae (1 species), Ammotheidae (3 species), Callipallenidae (3 species), Phoxichilidiidae (2 species) and Endeidae (1 species) - are reported in the present study. Out of these ten species, four are first records from Pakistan, including a new species, Achelia karachiensis sp. nov. Intertidal zoanthid colonies have been found to provide shelter and food to a large and diverse Pycnogonid population at Sandspit and the Buleji, Karachi coast. This study highlights the significance of the intertidal fauna of pycnogonids of these areas and contributes to our understanding of the species diversity from the Karachi coast.